Improved antibody pharmacokinetics by disruption of contiguous positive surface potential and charge reduction using alternate human framework - Romain Ollier; Aline Fuchs; Florence Gauye; Katarzyna Piorkowska; Sébastien Menant; Monisha Ratnam; Paolo Montanari; Florence Guilhot; Didier Phillipe; Mickael Audrain; Anne-Laure Egesipe; Damien Névoltris; et al. (Taylor & Francis Group, 2023)
ABSTRACTOptimal pharmacokinetic (PK) properties of therapeutic monoclonal antibodies (mAbs) are essential to achieve the desired pharmacological benefits in patients. To accomplish this, we followed an approach comprising structure-based mAb charge engineering in conjunction with the use of relevant preclinical models to screen and select humanized candidates with PK suitable for clinical development. Murine mAb targeting TDP-43, ACI-5891, was humanized on a framework (VH1-3/VK2-30) selected based on the highest sequence homology. Since the initial humanized mAb (ACI-5891.1) presented a fast clearance in non-human primates (NHPs), reiteration of humanization on a less basic human framework (VH1-69-2/VK2-28) while retaining high sequence homology was performed. The resulting humanized variant, ACI-5891.9, presented a six-fold reduction in clearance in NHPs resulting in a significant increase in half-life. The observed reduced clearance of ACI-5891.9 was attributed not only to the overall reduction in isoelectric point (pI) by 2 units, but importantly to a more even surface potential. These data confirm the importance and contribution of surface charges to mAb disposition in vivo. Consistent low clearance of ACI-5891.9 in Tg32 mice, a human FcRn transgenic mouse model, further confirmed its utility for early assessment and prediction of human PK. These data demonstrate that mAb surface charge is an important parameter for consideration during the selection and screening of humanized candidates in addition to maintaining the other key physiochemical and target binding characteristics.